Determination of Physicochemical and Microbial Properties of Some Dairy Cattle Products Sold in Kwami L.G.A of Gombe State - Hammari, Abubakar Muhammad; Bello, Aishatu; Umar, Balkisu Salihu; Aliyu, Bappah Mamuda; Gad, Ishaya Ajuji (Darul Yasin Al Sys, 2025)
This study evaluates the physicochemical and microbial properties of commonly consumed dairy products in Kwami Local Government Area (L.G.A.), with the objective of identifying potential health risks to consumers and informing regulatory oversight. A variety of dairy products—including milk, cheese, and yogurt—were sampled from multiple retail points and analyzed using standard analytical techniques in accordance with National Agency for Food and Drug Administration and Control (NAFDAC) and Codex Alimentarius guidelines. Physicochemical parameters assessed included pH, moisture, fat, protein content, and titratable acidity, while microbial analysis targeted pathogenic organisms such as Escherichia coli, Staphylococcus aureus, and Listeria monocytogenes. Results revealed significant variation in physicochemical properties, with protein content ranging from 9.80 ± 0.01% to 11.3 ± 0.82%, high moisture levels (70.5 ± 0.61% to 75.5 ± 0.61%), and elevated titratable acidity (0.5254 ± 0.03% in fresh milk to 2.6800 ± 0.02% in Kindirmo). Mean pH values were 3.50 and 4.55 for fresh milk and Kindirmo, respectively. Microbial screening detected high levels of contamination, including Staphylococcus aureus (3.00 × 10⁵ CFU/ml), Escherichia coli (8.0 × 10⁶ CFU/ml), Bacillus subtilis (2.80 × 10⁶ CFU/ml), and Lactobacillus bulgaricus (5.0 × 10⁵ CFU/ml), with some strains exhibiting antibiotic resistance. These findings underscore serious public health concerns and emphasize the urgent need for strengthened quality control measures, regulatory enforcement, and public awareness to enhance dairy safety in the region.